Optimization of Confidentiality, Integrity, and Availability Through Network Segmentation: A Comparative Simulation Study - Maria Rachel Kesya Makarena; Jasmine Alya; Aundrel Aza Sadira; Vorian Gustaf Sumampow; Johannes Hamonangan Siregar (Jurnal Sistem Informasi dan Teknologi Informasi, 2025)
Flat network architectures present significant security and efficiency challenges, exposing organizations to heightened risks of cyberattacks, including data breaches and service disruption, while impeding optimal network performance. This inherent vulnerability directly conflicts with the fundamental information security objectives of Confidentiality, Integrity, and Availability (CIA Triad). To address these critical issues, this research investigates the strategic implementation of Virtual Local Area Network (VLAN) segmentation as a mechanism to concurrently enhance security and operational performance. The study employs an experimental, simulation-based methodology using Cisco Packet Tracer software to design and evaluate a functionally segmented network topology. The model incorporates role-based traffic isolation and enforces precise access policies through the application of Extended Access Control Lists (ACLs) on inter-VLAN routing points. Simulation analysis demonstrates that the proposed architecture yields a dual benefit: a 70% reduction in broadcast domain traffic and up to a 50% decrease in communication latency, substantially improving network efficiency and stability. From a security perspective, the logical isolation of segments successfully contained and mitigated prevalent Layer 2 threats, including packet sniffing and ARP poisoning attacks, thereby strengthening data confidentiality and network integrity. The findings conclusively establish that VLAN segmentation, when integrated with granular ACL policies, serves as a foundational and highly effective strategy. It provides a robust technical framework for enforcing the CIA Triad, transforming network infrastructure from a vulnerable, flat entity into a secure, performant, and resilient organizational asset.